APLIKASI SISTEM INFORMASI GEOGRAFIS TERHADAP MANAJEMEN TRANSPORTASI DARI TPH KE PKS - Ibnu Azhar Putra; Betti Yuniasih; Hangger Gahara Mawandha (Program Studi Agroteknologi INSTIPER, 2021)
This study aims to create a transportation management database, create a participatory map of the harvest path from the TPH to Mill and create a transportation management model in palm oil plantations. The study was conducted at PT. Langkat Nusantara Kepong (LNK) Tanjung Beringin Estate, Hinai District, Langkat Regency, North Sumatra. This research was conducted in May - June 2019. This research was conducted by direct measurement in the field and navigation analysis. Direct measurements in the field are done by calculating the distance from TPH to Mill, calculating the average speed of trucks when carrying FFB to Mill, calculating truck time from TPH to Mill. To measure the distance done using GPS Garmin then data from GPS is entered and analyzed with the ArcGIS program. Navigation analysis is carried out using Network Analysis in ArcGIS, where the work of Network Analysis will find the most effective and efficient way. Roads in Tanjung Beringin Gardens are distinguished by their functions as HW (Highway), MR (Main Road), CR (Collection Road) and BR (Boundrest Road). Map of the FFB transportation path from TPH to Mill via the CR line which then passes the MR, and passes the HW that corresponds to the truck lane. The results of research conducted by direct measurement in the field of FFB to Mill are already effective and efficient compared to navigation analysis. Keywords: Navigation Analysis, GIS, TPH, harvest transportation, palm oil